Developing a Hyperpersonal Communication Model in Sexting Behavior: A Mixed Methods Study of Digital Intimacy in Indonesia - Budiawan Budiawan; Alvianus Dengen (MASI Mandiri Edukasi, 2026)
Sexting as a form of digital sexual self-disclosure has become increasingly common among young people in Indonesia. The Hyperpersonal Communication Model (HCM) theory was originally developed to explain text-based online interaction, while contemporary digital intimacy now involves multimodal communication, risk awareness, privacy concerns, and trust negotiation. This study aims to develop a contextual HCM model by integrating digital sexual self-disclosure, perceived digital intimacy, selective self-presentation, idealized perception, and risk awareness in explaining sexting behavior in Indonesia. This research used a mixed-methods, sequential, explanatory design. The quantitative phase involved a survey of 300 respondents aged 18–35 years in five major Indonesian cities and was analyzed using SPSS Version 27. The qualitative phase involved in-depth interviews with 20 selected participants to explore the subjective meanings of sexting experiences. The findings show that Digital Sexual Self-Disclosure is the strongest predictor of Perceived Digital Intimacy (β=0.412), while 68.7% of respondents reported having engaged in sexting. Risk Awareness was also positively correlated with Perceived Digital Intimacy (r=0.387), suggesting that risk awareness may encourage explicit boundary negotiation and trust-building rather than reduce intimacy. Qualitative findings reveal a gradual escalation pattern from text to photo and video, with each stage shaped by trust tests and privacy considerations. This study expands HCM theory by proposing trust negotiation as a fifth mechanism alongside Walther’s four classical mechanisms, emphasizing trust-based gradual disclosure shaped by Indonesian socio-cultural norms. Practically, the findings highlight the need for digital literacy programs that address consent, boundary negotiation, privacy protection, and safer intimate communication among young adults.